Epidemiological Analysis of the Occurrence of Tick-borne Diseases at the Independent Public Health Care Facility in Bielsk Podlaski - Katarzyna Snarska; Ewa Chmur; Cecylia Dolińska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Ticks can infect people with numerous pathogens causing various infectious (viral, bacterial) or invasive (parasitic, fungal) diseases. Aim. The main objective of the present work included the epidemiologic analysis of the occurrence of tick-borne diseases at the Independent Public Health Care Facility in Bielsk Podlaski. Material and Methods. An analysis of medical documentation stored in the hospital’s IT database of patients hospitalized in 2016, 2017 and 2018 was performed. Sixty-six patients admitted to the Observation and Infectious Disease Ward diagnosed with tick-borne diseases, were qualified for the study. Results. Analysis of the data showed that Lyme disease was diagnosed most often. It affected mainly middle-aged and elderly men. The second most-often diagnosed illness was TBM characterized by its seasonality. No other tick-transmitted diseases were recorded. Although not all patients were aware of having been bitten by a tick, their symptoms allowed the diagnosis of tick-related illnesses. After treatment relevant to each ailment all patients were discharged in a good state of health. Conclusions. The completed retrospective analysis of the documentation of hospitalized patients shows consistency with the work of other authors both with respect to the frequency of tick-borne disease diagnoses and the most often reported symptoms. It also confirms an upward trend with respect to tick-borne disease hospitalizations. (JNNN 2020;9(2):51–58)